Juvenile Osteochondritis Dissecans of the Knee Joint: Midterm Clinical and MRI Outcomes of Arthroscopic Retrograde Drilling and Internal Fixation with Bioabsorbable Pins. (December 2021) - Komnos, Georgios; Iosifidis, Michael; Papageorgiou, Fotios; Melas, Ioannes; Metaxiotis, Dimitrios; Hantes, Michael
Objective: This study aimed to assess the clinical and radiographic outcomes of juvenile patients who suffered from stage II or III osteochondritis dissecans (OCD) of the knee and underwent arthroscopic retrograde drilling and internal fixation with bioabsorbable pins. Design: Medical and radiological records from patients aged 11 to 16 years, who underwent arthroscopic treatment for OCD lesions of the knee in 2 tertiary hospitals, were retrospectively reviewed. The procedure was indicated by persistent pain and by magnetic resonance imaging (MRI). All patients underwent retrograde drilling and arthroscopic fixation of the lesion with bioabsorbable pins. MRI was conducted at least 1 year postoperative in all patients to evaluate healing. Functional outcomes were evaluated through the Visual Analogue Scale (VAS) for pain, Lysholm, and IKDC (International Knee Documentation Committee) scores. Results: A total of 40 patients, with an average age of 13.1 years (range = 11-16 years) and an average follow-up of 6.6 years (range = 3-13 years) were reviewed. MRI findings confirmed the healing of the lesion in 36 out of the 40 (90%) patients. In particular, the healing rate was 95% (20/21) and 84% (16/19) for stage II and stage III, respectively. Lysholm, IKDC, and VAS scores revealed a statistically significant improvement ( P < 0.05) at final follow-up in comparison to preoperative status. No infection, knee stiffness, or other complication was recorded. Conclusions: Retrograde drilling combined with internal fixation with bioabsorbable pins, of stages II and III OCD lesions of the knee provides good to excellent outcomes to juvenile patients, with a high healing rate.